Solvent extraction and selective separation of base metal ions by means of pyrazole- and imidazole-pyridinyl ligands - Pearce, Brendan Harold (Stellenbosch : Stellenbosch University, 2020, 2020)
Thesis (PhD)--Stellenbosch University, 2020